Guidelines for daily carbohydrate intake: do athletes achieve them? - Burke, L. M.; Cox, G. R.; Culmmings, N. K.; Desbrow, B. (Sports Medicine, 2001)
Official dietary guidelines for athletes are unanimous in their recommendation of high carbohydrate (CHO) intakes in routine or training diets. These guidelines have been criticised on the basis of a lack of scientific support for superior training adaptations and performance, and the apparent failure of successful athletes to achieve such dietary practices. Part of the problem rests with the expression of CHO intake guidelines in terms of percentage of dietary energy. It is preferable to provide recommendations for routine CHO intake in grams (relative to the body mass of the athlete) and allow flexibility for the athlete to meet these targets within the context of their energy needs and other dietary goals. CHO intake ranges of 5 to 7 g/kg/day for general training needs and 7 to 10 g/kg/day for the increased needs of endurance athletes are suggested. The limitations of dietary survey techniques should be recognised when assessing the adequacy of the dietary practices of athletes. In particular, the errors caused by under-reporting or undereating during the period of the dietary survey must be taken into account. A review of the current dietary survey literature of athletes shows that a typical male athlete achieves CHO intake within the recommended range (on a g/kg basis). Individual athletes may need nutritional education or dietary counselling to fine-tune their eating habits to meet specific CHO intake targets. Female athletes, particularly endurance athletes, are less likely to achieve these CHO intake guidelines. This is due to chronic or periodic restriction of total energy intake in order to achieve or maintain low levels of body fat. With professional counselling, female athletes may be helped to find a balance between bodyweight control issues and fuel intake goals. Although we look to the top athletes as role models, it is understandable that many do not achieve optimal nutrition practices. The real or apparent failure of these athletes to achieve the daily CHO intakes recommended by sports nutritionists does not necessarily invalidate the benefits of meeting such guidelines. Further longitudinal studies of training adaptation and performance are needed to determine differences in the outcomes of high versus moderate CHO intakes. In the meantime, the recommendations of sports nutritionists are based on plentiful evidence that increased CHO availability enhances endurance and performance during single exercise sessions.